La prison Winter. Revitaliser le (sombre) patrimoine sherbrookois - Sophie Abdela; David Lacoste; Yanick Laverdière (Criminocorpus)
Opened in the province of Quebec in 1869, the Sherbrooke common jail (Winter Jail) quickly acquired a reputation for being harsh, severe and, above all, unhealthy: despite various phases of renovations throughout the building’s history, living conditions improved very little and led to its ultimate closure in 1990. Since then, the Winter Jail has been abandoned. The Sherbrooke History Museum wishes to acquire the building in order to transform it into an interpretation center and organize exhibitions, guided tours and even escape games. In addition to the financial issues related to the project, the revitalization of the Winter Jail raises fundamental questions. Why should the building be saved? This article outlines the planned conversion of the Winter Jail into a museum and the transmission strategies that will help avoid the pitfalls of « dark tourism ».